Initial provisions of state financial control in the system of state management of economic security of Ukraine - Levytskyi, Yaroslav (Public Policy and Accounting, 2024)
State financial control is a key factor for effective financial management, economic security and welfare of society, especially in conditions of instability. It provides the control function of the state, counteracting offenses and corruption. In Ukraine, the growth of financial violations is due to a weak theoretical and methodological base and outdated forms of control, which reduces the effectiveness of state financial control. The study substantiates the content of control from the perspective of public administration, identifies the object, subject and subject. In the course of the study, the purpose and general objectives of state financial control are determined. Priority tasks are justified, which are determined by modern political, economic and international factors. A set of principles of state financial control is determined: legality, impartiality, independence, systematicity, objectivity, transparency, efficiency, planning, publicity, obligation.